The Degree to Which Earth and Environmental Science Teachers Practice Twenty-First-Century Skills in Jordan - Omar Riyad Al-Qaqah; Hussein Abdellateef Ba'arah (Britain International for Academic Research (BIAR) Publisher, 2022)
The study was aimed at revealing the degree to which earth and environmental science teachers practice the skills of the twenty-first century in Jordan. The researchers used the descriptive approach. The study population consisted of all 886 teachers of earth sciences and environment in the northern region of Jordan. The sample study was selected in a simple random manner, with 201 teachers and 23% of the study population. The researchers used the 21st Century Skill identification study instrument applied to the sample study. The results of the study showed that the degree of the practice of the 21st Century Earth and Environment Science Teachers was at the intermediate level and at average (3.52). The results also showed that there were no statistically significant differences in the extent to which Earth and Environment Science Teachers practiced twenty-first-century skills in the light of their gender, scientific qualification, and experience.